Global, national and regional prevalence, and associated factors of ocular trauma: A protocol for systematic review and meta-analysis. Issue 35 (28th August 2020) - Bian, Xiaoyan; Xu, Shuang; Song, Yuli; Wang, Yuye; Zhao, Bin; Zhong, Yifan; Liu, Lei; Hu, Yudong
Abstract: Background: Ocular trauma is a common eye disease and one of the main causes of blindness. There is a dearth of data on a summary and meta-analysis on the global epidemiology of the disease. Therefore, this systematic review protocol aims to propose the first systematic review and meta-analysis to synthesize existing evidence on the global prevalence and associated factors of ocular trauma worldwide. Methods: A systematic search will be performed according to the following databases: PubMed, Web of Science, Chinese National Knowledge Infrastructure (CNKI), Weipu, and Wanfang. Cross-sectional, case-control, and cohort studies reporting on the prevalence and risk factors of ocular trauma will be included. The primary outcome will be the prevalence in global, regional, and national ocular trauma. Study searching, data extraction, and quality evaluation will be performed by 2 reviewers, independently. Appropriate meta-analysis will then be used to pool studies. STATA software package v 12.0 (Stata Corporation, College Station, TX) and R (version 3.4.1; R Foundation for Statistical Computing, Vienna, Austria) software will be used for all statistical analyses. Results: This study will provide a high-quality synthesis to examine the prevalence and associated factors of ocular trauma worldwide. Furthermore, current study will project disease estimates in the next 50 years. Conclusion: This systematic review and meta-analysis will provide first evidence to evaluate the burden of ocular trauma in the general population. Ethics and dissemination: This systematic review and meta-analysis of randomized controlled trials does not require ethical recognition, and the results of this paper will be published in an open access, internationally influential academic journal. Trial registration number: CRD42020189166